Monitoring National Payment Schemes: Some Global Practices abd Turkish Payment Scheme - TROY - Çetiner, Emine Müge; Kayalıdereden, Didem (My University, 2018)
Since the beginning of 21.st century, disruptive innovations in technology have ushered a new era in payment systems. This article has been inspired by TROY, which is the “Turkey’s Payment Method” in Turkish, and it aims to put the local payment schemes on the map of Turkish Academia by exemplifying some best practices, why have been needed and what are the expectations lying behind them. It consists of five chapter which starts with the historical framework of modern cards payment industry and popularized concept; “cashless society”. In the second part, the answer to the question of “who are the key participants in a payment system?” is examined. In this context, modernized definition of the payment is made by shortly introducing some of new and ever-changing payment methods, namely mobile payments or crypto-currencies. Meanwhile, some countries have established their own payment schemes to gain advantages in the forthcoming technology race. Major national payment schemes are listed and occasionally analyzed in terms of implementations. Hereby, TROY is reviewed concisely and explained in terms of main features as a noteworthy implementation. Finally, despite of the mighty global payment actors, basis of existence and future value of national schemes are summarized.
Keywords: Payment; National Payment Schemes; Troy; Cashless Society; Innovation; Ödeme; Ulusal Ödeme Planları; Kuyumcu Tartısı; Nakitsiz Toplum; Yenilik